Sustainability in your backyard - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
People's farming workbook. Second revised edition. David Philip Publishers-CTA copublication. 1998. 256 pp. ISBN 0 86486 431 0 CTA number 939. 20 credit points.